Os limites da admissibilidade da prova ilícita no processo penal brasileiro - Gusmão, Victor Santos (2021)
The inadmissibility of unlawful evidence is one of the most important guarantees in the context of criminal proceedings, considering that it is a central issue for the basis of judicial decisions. Thus, the prohibition of illegal evidence, a true constitutional guarantee, stands in a prominent place in the national legal system. However, as with other constitutional guarantees, the application of the prohibition of illegal evidence cannot take place in an absolute manner, under penalty of causing situations incompatible with the values of justice adopted by society. In this way, the analysis of illegal evidence and its behavior in the process becomes dear to both legal practitioners and other members of society, considering that, eventually, anyone can appear as a party in criminal proceedings. This work, therefore, brings as its theme the limits of the admissibility of illicit evidence in the Brazilian criminal procedure, analyzing them in order to reach the general objective of understanding what led to the establishment of each exception, as well as to delimit the scope of each reservation . Therefore, this exploratory work starts from a qualitative approach, which emphasizes the bibliographical research pertinent to the topic, establishing the following specific objectives: to describe the main characteristics of the treatment of evidence and its illegality in the Brazilian criminal procedure, passing through the introductory concepts; expose the exception to the inadmissibility of illicit evidence by deriving from the use of the theory of inevitable discovery; and detailing the functioning of the principle of proportionality and its use to admit illicit evidence in criminal proceedings. Finally, this research concludes for the existence of two possibilities for admitting illicit evidence in the Brazilian criminal process, reaffirming, in the end, the limits imposed by doctrine and jurisprudence on the subject.